A Comprehensive Review of Voltage Source Converters-Based FACTS Controllers in Hybrid Microgrids - Maloth Hussen; Thirumalaivasan Rajaram (IEEE Access)
This article presents a comprehensive review of voltage source controller-based Flexible Alternating Current Transmission System (FACTS) controllers and their important role in enhancing the performance of hybrid microgrids. The primary objectives of this review are to explore the various applications of voltage source controllers, investigate advanced control strategies used in their integration, and evaluate their impact on power quality, stability, and overall efficiency in hybrid microgrid scenarios. The review exploit a systematic approach, synthesizing existing literature on FACTS controllers, with a focus on Static Synchronous Compensators (STATCOMs), Static Synchronous Series Compensator (SSSC), Interline Power Flow Controller (IPFC), and Unified Power Flow Controllers (UPFCs). This review emphasizes the significant role of VSC-based FACTS controllers in enhancing the stability, reliability, and efficiency of hybrid microgrids. The review covers various control strategies, integration challenges, and optimization techniques, offering insights into the latest advancements and future research directions. The capability of STATCOMs to regulate voltage and reactive power, while SSSC concentrates on series compensation for enhanced power transfer capability. UPFCs are perfect for complex microgrid management because they provide complete control over both reactive and real power. IPFCs, designed for multi-terminal operation, further enhance controllability. The focus is on acknowledging the development of voltage source controllers, starting from conventional control techniques to the integration of more advanced methods like optimization strategies, adaptive control, and machine learning-based approaches. This review highlights the significance of FACTS controllers, particularly VSCs, in ensuring reliable and efficient operation of hybrid microgrids, hence further empowering the wider adoption of renewable energy sources.